Early growth, dominance acquisition and lifetime reproductive success in male and female cooperative meerkats - English, Sinead (Blackwell Publishing Ltd, 2013)
In polygynous species, variance in reproductive success is higher in males than females. There is consequently stronger selection for competitive traits in males and early growth can have a greater influence on later fitness in males than in females. As yet, little is known about sex differences in the effect of early growth on subsequent breeding success in species where variance in reproductive success is higher in females than males, and competitive traits are under stronger selection in females. Greater variance in reproductive success has been documented in several singular cooperative breeders. Here, we investigated consequences of early growth for later reproductive success in wild meerkats. We found that, despite the absence of dimorphism, females who exhibited faster growth until nutritional independence were more likely to become dominant, whereas early growth did not affect dominance acquisition in males. Among those individuals who attained dominance, there was no further influence of early growth on dominance tenure or lifetime reproductive success in males or females. These findings suggest that early growth effects on competitive abilities and fitness may reflect the intensity of intrasexual competition even in sexually monomorphic species.